SILENT VALLEY — THE NEED FOR WILDLIFE CONSERVATION - Mahajan, K.K. (SCHOOL SCIENCE, 2012)
For an average human being wildlife conservation means setting up some national parks to protect areas of natural beauty; to establish sanctuaries for the preservation of one or more endangered species of animals, to create botanical gardens for maintaining a vast collection of plants for research and educational purposes etc. But there is a good number of intelligent and well-informed persons, who know that every living organism on this earth is a mini chemical factory of its own kind with tremendous potential and also each species in the wild is a rich living genetic resource which provides a vital component for the whole life support system of the universe